O hipertexto eletrônico de meio ambiente : estratégias de leitura e navegação - Burgos, Taciana de Lima (2006)
The incorporation of computing in class instigate the use of the Internet and websites as a content support in the teaching/leaning process. This kind of practice had challenged the students to read through eletronic hypertextual means. In that way, we re trying to undestand which strategies of reading and navigation the students of the second and third grade of highschool levels are using when reading electronic hypertexts from the www.ambientebrasil.com.br website. The research took place in the Escola Estadual Jerônimo Rosado in Mossoró RN. Our theoretical base was estructured on the digital Technology (electronic hypertext estructure and it s navigation modes), in applied linguistics (act of reading) and in cognition (interaction of the reader with the text and the use of reading strategies in the virtual computing enviroment). The applied methodology was the case analysis which was developed with the reunion of collected data through qualitative reseach questionaries, direct observations and video recording sessions. The research demonstrates that reader s ability in the act of navigating on virtual sites activates his/her reading strategies. Also shows how the semantic architecture of the hyperlinks can interfere directly over the strategies of reading and navigation in specific websites. Our research also intend to demonstrate that the student use his strategies of linear text reading when are not accustomed to use the reading through websites in a regular basis. The investigation concludes observing that the amount of hypertexts per pages and the inappropriate use of the multimedia elements were harmful to the reading fluency